Permainan Tradisional Bebencaran Terhadap Kemampuan Fisik Motorik Anak Usia 5-6 Tahun - Hilda Putri Nailil Izzah (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
This research aims to analyze the impact of games on the physical motor skills of children aged 5-6 years at RA Muslimat NU Darul Ulum Ngembes. The type of approach used is a qualitative descriptive approach. Data collection techniques are observation, interviews, and documentation. The data collection instruments used were researchers, observation sheets, and interviews. Based on several research results, it shows that boy-boyan games are beneficial for the physical motor development of young children at RA Muslimat NU Darul Ulum Ngembes.